Principles of Learning Organizations and It`s Role to achieve Group Working: A Viewed Study in Public Company for Webbing Industries in Hilla - العابدي علي رزاق; حسن ابراهيم محمد; الشمري سرمد حمزة (Journal of Economics and Administrative Sciences, 2014)
Organizations must interact with the environment around them, so the environment must be suitable for that interaction. These companies are now trying to become Learning Organizations because it try to face that challenges may rise from its environments. The Learning Organization is a concept that is becoming an increasingly widespread philosophy in modern companies, from the largest multinationals to the smallest ventures. What is achieved by this philosophy depends considerably on one’s interpretation of it and commitment to it. This study gives a definition that we felt was the true ideology behind the Learning Organization and Group Working. A Learning Organization is one in which people at all levels, individuals and collectively, is continually increasing their capacity to produce results they really care about. At the heart of a learning organization lies the belief that enormous human potential lies locked and undeveloped in our organizations. This research was applied at one of the Iraqi public sector, which is Public Company for Webbing Industries in Hilla. The central conclusion is the conviction that when all members of an organization fully develop and exercise their essential human capacities, the resulting congruence between employee empowerment, knowledge participation, environmental scanning and human involvement will release this potential and helpful at group working. Therefore, the behavior side of technical and managerial performance is very importance for reaching to group working. Organizations must to give its` employee some of freedom at workplace and managing of their performance, but that matter should be achieve benefits for both of organization and its` employee